Pengaruh Pasar Digital Terhadap Omset Penjualan Pakaian di Pasar Batuah Martapura - Yuliana Hidayati Asybary; Mukhlis Kaspul Anwar; Lola Malihah (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2023)
ABSTRACT This study aims to determine how the digital market influences the turnover of clothing sales in the Batuah Martapura market. This research was conducted on the Batuah Martapura market traders. The population of respondents in this study are clothing traders who use the digital market, totaling 27 people with the snowball sampling method. Data collection techniques in this study were in the form of questionnaires and interviews. The analysis technique used in this research is quantitative by using validity test, reliability test, normality test, linearity test, t test and coefficient of determination test. The results of this study indicate that there is a significant untested influence of the Digital Market on the Turnover of Clothing Sales at the Batuah Martapura Market. It is shown by the results of the t-test that the result of tcount is (- 285) and the significance value (Sig.) is 0.778 so that tcount = (-285) < ttable = 1.708 and the value of Sig. = 0.778 > = 0.1. Because the value (-285) < 1.708 and 0.778 > 0.1, it can be concluded that the hypothesis H0 is accepted and H1 is rejected. So the results of the analysis from the t-test can be said that the digital market is not tested significantly on the sales turnover of clothing traders who use the digital market at Batuah Martapura Market. The coefficient of determination value is 0.003, this means that the variation of digital market changes (X) is not tested significantly on the sales turnover of traders in the Batuah Martapura market (Y) is 0.3%, while the rest is influenced by other variables in this study. Keywords: Digital Market, Traditional Market, Sale Omzet.